2021
DOI: 10.1080/10717544.2021.1872740
|View full text |Cite
|
Sign up to set email alerts
|

Cubogel as potential platform for glaucoma management

Abstract: The aim of this work is to survey the potential of cubogel as an ocular dosage form to boost the corneal permeability of Dorzolamide Hydrochloride DZ; an antiglaucomal drug. DZ-loaded cubosomal dispersions were prepared according to Box-Behnken design, where the effect of independent variables; Monoolein MO concentration (2.5, 5 and 7.5%w/w), Pluronic V R F127 concentration (0.25, 0.5 and 0.75%w/w) and magnetic stirrer speed of (400, 800 and 1200 rpm) was studied on PS (nm), Zp (ÀmV) and Q 2 h (%) respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…[20,21] Conventionally, the release of DOX which loaded in MIL100 could be excited by low pH condition and abundant H 2 O 2 in tumour. [22] In this study we found that lower pH and GSH can synergistically promote drug release from the DOX@PEG-MIL100 nanoparticles, thus to realize the pH and GSH dualsensitive drug deliver system.…”
Section: Introductionmentioning
confidence: 75%
“…[20,21] Conventionally, the release of DOX which loaded in MIL100 could be excited by low pH condition and abundant H 2 O 2 in tumour. [22] In this study we found that lower pH and GSH can synergistically promote drug release from the DOX@PEG-MIL100 nanoparticles, thus to realize the pH and GSH dualsensitive drug deliver system.…”
Section: Introductionmentioning
confidence: 75%
“…All runs except for runs 4, 7, 8, 9 are within the accepted USP drug ranges which varies from 85–115%. 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
“…Specimens were cleared by xylene and inserted in paraffin at 56 °C in hot air oven for 24 h. Sledge microtome is used to prepare paraffin bees wax tissue units at 4 µm thickness. The achieved tissue sections were gathered on glass slides, deparaffinized, stained by hematoxylin and eosin stain for usual assessment via the light electric microscope (Leica, Cambridge, UK) (Sayed et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%